O ensino de história e cultura afro-brasileira e africana: a importância da formação e a efetivação de um currículo - Dias, Ione Aparecida Duarte Santos (2019)
ABSTRACT: The present work aims to follow how the formation of the teacher has contributed to the elaboration of a curriculum that contemplates the applicably of the Law number 10.639/2003, in the schools of city of Cariacica/ES. We hypothesize that there are few or nonextente classes that guarantee the applicability of Law. To dialogue with the theme we elected some theorists as Freire (1996, 2004), Santos (2007, 2016), Munanga (2003, 2008), Brandão (1984), among others. For the accomplishment of this work, the participant research/action research was used. As methodological ways, we researched and analyzed the legislation aimed at combating racism and discrimination in the municipality of Cariacica. We conducted a qualitative analysis of continuing education for Ethnic-Racial Relations Education in the municipality of Cariacica. We participated in the formation of the course “Training and Research for Education of Ethnic-Racial Relations”, Federal University of Espirito Santo , as well as accompanying its developments within some educational institutions in the municipality of Cariacica. In summary, the demands presented pointed to the need for the implementation of a curriculum that includes Law number 10.639/2003 and the importance of teacher education in the process of confronting racism, since, with more than 15 years of Law number 10.639/2003 the practices proposed in schools do not yet address the issues cited in the Law.